2019
DOI: 10.1039/c9ra01289c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(norepinephrine)-coated FeOOH nanoparticles as carriers of artemisinin for cancer photothermal-chemical combination therapy

Abstract: Tumor-specific FeOOH@PNE-Art nanoparticles were fabricated that showed high efficacy of photothermal-chemical combination therapy and low toxicity to normal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…A number of reports have demonstrated the advantages of PNE coating techniques over PDA coating, in terms of coating uniformity. Compared to that with PDA, the PNE coating provides a more uniform and well-defined nanolevel coating on the surfaces. ,, Hence, it is often recommended as a more preferable chemical approach for material surface coatings. ,, It is expected that the surface of the resulting PNE-coated nanomaterials may exhibit more reproducible and consistent characteristics in forming dynamic covalent bonds with the polymeric networks.…”
Section: Chemical Strategies: Nanocomposite Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have demonstrated the advantages of PNE coating techniques over PDA coating, in terms of coating uniformity. Compared to that with PDA, the PNE coating provides a more uniform and well-defined nanolevel coating on the surfaces. ,, Hence, it is often recommended as a more preferable chemical approach for material surface coatings. ,, It is expected that the surface of the resulting PNE-coated nanomaterials may exhibit more reproducible and consistent characteristics in forming dynamic covalent bonds with the polymeric networks.…”
Section: Chemical Strategies: Nanocomposite Hydrogelsmentioning
confidence: 99%
“…374,377,378 Hence, it is often recommended as a more preferable chemical approach for material surface coatings. 375,379,380 It is expected that the surface of the resulting PNE-coated nanomaterials may exhibit more reproducible and consistent characteristics in forming dynamic covalent bonds with the polymeric networks.…”
Section: Nanocarbon-based Hydrogelsmentioning
confidence: 99%
“…For example, the pH-responsive DHA-GO-TF and TF-8arm-PEG-DHA delivery systems both showed higher solubility, enhanced tumor delivery specificity, minimal side-effects, and superior tumor growth restrained ability in vivo [184,185]. Third, the release of metal ions by polymer-based nanoparticles was shown to enhance ART or ART derivative-induced tumor inhibition [187][188][189].…”
Section: Polymer-based Art-loaded Nanoparticlesmentioning
confidence: 99%
“…In vivo evidence showed that the anticancer efficacy of DHA@HPDA-Fe was 3.05 times higher compared with free DHA (Dong et al, 2019). Besides, some other biocompatible polyphenolic compounds such as tannic acid have similar binding and releasing futures toward Fe 2+ and Fe 3+ (Kell, 2009;Du et al, 2019;He et al, 2019). These polymers could also be considered for construction of ART's nanotherapeutics, but the related research is still rare.…”
Section: Iron-containing Soft Matters For Arts Delivery and Activationmentioning
confidence: 99%